Polychaetes (Annelida) from Sepetiba Bay (Brazil): an update on species occurrences - Ricardo Álvarez; Andrielle Raposo Rodrigues; João Gabriel Rebello; Vinícius da Rocha Miranda; Ana Claudia dos Santos Brasil (Ocean and Coastal Research)
Members of several polychaete families inhabit rocky shores, including syllids, serpulids, eunicids, nereidids, and sabellids. The primary studies on consolidated substrates conducted in Sepetiba Bay (Rio de Janeiro, Brazil) date back to 2004, with multiple taxonomic studies having been carried out since then. In this study, we present an updated checklist on polychaetes from hard substrates in Sepetiba Bay, together with an identification key for the species. We also discuss the status and distribution of certain species along the Brazilian coast. Myrianida pachycera, Branchiomma bairdi, Branchiomma coheni, and Branchiomma conspersum represent new occurrences in Brazil. We extend the distribution of Proceraea anopla to Southeastern Brazil, and report 33 new records for Sepetiba Bay. We identify Halosydna glabra, Oxydromus obscurus, Oxydromus pugettensis, Marphysa sanguinea, Lysidice ninneta, Spirobranchus americanus, Polydora ciliata, Pseudonereis variegata, Nereis cf. oligohalina, and Schistomeringos rudolphi as requiring taxonomic revision, all of which have been recorded previously in Sepetiba Bay. However, the specimens we examine in this study differ from the original descriptions, indicating that a more comprehensive assessment of the respective species is needed along the Brazilian coast.